DRUG DELIVERY BASED ON BUCCAL ADHESIVE SYSTEMS - A REVIEW - SWEET NASKAR,; SANJIT KR. ROY,; KETOUSETUO KUOTSU, (International Journal of Pharma and Bio Sciences, 2013)
Buccal delivery involves the administration of the desired drug through the buccal mucosal membrane lining of the oral cavity.The objective of this article is to review buccal drug delivery by discussing the structure and environment of the oral mucosa and highlighting the mechanisms of drug permeation and methodology in evaluating buccal formulations. This review also highlights a brief description of advantages, limitations of buccal drug delivery and theories involved in mucoadhesion. Additionally, we discuss on the new generation of mucoadhesive polymers such as thiolated polymers, lectins, followed by the recent mucoadhesive formulations for buccal drug delivery.